Collective autobiographical reflexivity on active and compassionate citizenship in the COVID-19 crisis - Cheong, Stella Mi-Cheong (Archīum Ateneo, 2021)
Since the outbreak of the coronavirus pandemic, socio-economic inequalities have become exacerbated and COVID-19 related hate crimes have increased. This paper explores how citizenship education might be reimagined in response to this context, with the vision of rebuilding a more equitable and compassionate society. By using a collective autobiographical writing approach, this study documented six different autobiographical reflexivities of citizenship education scholars who were from different parts of the world: China, South Korea, the Philippines, the United States, Nepal and the United Kingdom. It also observed the way the pandemic played out in the location where they were situated during the research as well as how it played out in their countries of origin, and further, how it affected the civic development in each context. The scholars' range of autobiographical expressions resulted in insights for developing a type of citizenship education, namely, education for active and compassionate citizenship.